The experience of rural families in the face of cancer - Nara Marilene Oliveira Girardon-Perlini; Margareth Ângelo
ABSTRACT Objective: To understand the meanings of cancer within the experience of rural families and how such meanings influence family dynamics. Method: Qualitative study guided by Symbolic Interactionism as a theoretical framework and Grounded Theory as a methodological framework. Six rural families (18 participants) undergoing the experience of having a relative with cancer participated in the interview. Results: Constant comparative analysis of data allowed the elaboration of an explanatory substantive theory, defined by the main category Caregiving to support the family world, which represents the family's symbolic actions and strategies to reconcile care for the patient and care for family life. Final considerations: Throughout the experience, rural families seek to preserve the interconnected symbolic elements that provide support for the family world: family unit, land, work and care.